Implementing the Contextual Approach in Mathematics Learning to Enhance Students' Problem Solving Abilities: Penerapan Pendekatan Kontekstual dalam Pembelajaran Matematika untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa - AriniHariyati; Rudi Purwanto (ASIAN: Indonesian Journal of Learning Development and Innovation, 2023)
This research aims to investigate the effectiveness of implementing the contextual approach in mathematics learning to enhance students' problem-solving abilities. The research method used is an experimental study. The research sample consists of two classes, with VIIB as the experimental group and VIIA as the control group at SMN 2 Sakra. The experimental group undergoes mathematics learning with the contextual approach, while the control group follows a conventional approach. Data on students' mathematical problem-solving abilities are collected through pre- and post-implementation mathematics problem-solving tests within the contextual approach. The assessment instrument comprises mathematical problem-solving questions that require students to apply concepts in contextual situations. The collected data are analyzed using a t-test to compare the differences in students' problem-solving abilities between the experimental and control groups. The analysis results indicate that the group of students who underwent mathematics learning with the contextual approach achieved a significant improvement in problem-solving abilities compared to the control group that used a conventional approach. These results demonstrate that the contextual approach can facilitate the understanding of mathematical concepts and encourage students to apply problem-solving in real-world contexts. This research concludes that the implementation of the contextual approach in mathematics learning can enhance students' mathematical problem-solving abilities